Pseudomonas Aeruginosa a tenacious uropathogen: Increasing challenges and few solutions - Falah Hasan Obayes AL-Khikani; Aalae Salman Ayit (Biomedical and Biotechnology Research Journal, 2022)
No population in the world can be cleared from urinary tract infections (UTIs) that considered the most common bacterial infection globally, every year more than 150 million people suffering from acute or chronic UTI caused by various bacteria. It is among the most frequent health care-associated diseases. In patients with UTI, Pseudomonas aeruginosa deserves special attention since it can affect patients with serious underlying conditions. P. aeruginosa is a multidrug-resistant pathogen causing numerous chronic infections including urinary tract disorders. Infection caused by this organism is difficult to treat because of the presence of its innate resistance to many antibiotics and its ability to acquire further resistance mechanism to multiple classes of antibiotics, including beta-lactams, aminoglycosides, and fluoroquinolones; thus, the treatment option for these drug resistance pseudomonas are very limited. P. aeruginosa-induced UTIs continue to be linked with substantial mortality and morbidity. This adverse consequence is owing to our failure to create effective disease-prevention treatment methods, which is related to a lack of knowledge of resistance mechanisms. This study alerts researchers to the need to better understand the mechanisms of resistance in P. aeruginosa-caused UTIs to develop viable treatment options. The microbiological perspectives, virulence factors, epidemiology, mechanisms beyond antibiotic resistance, and antimicrobial sensitivity of P. aeruginosa in UTI are discussed in this review as well as future strategies to build basic information and clear vision to other researchers for more studies regarding this tenacious bacterium.